Facing climate change in the Marshall Islands - Rudiak-Gould, P (2011)
The Marshall Islands may be rendered uninhabitable by sea level rise and other consequences of global climate change within 50 years, a threat with which locals are increasingly familiar via educational events, firsthand environmental observation, and Biblical exegesis. This thesis explores Marshallese attitudes towards this spectre, in particular explaining why ‘ordinary’ Marshall Islanders (if not their government) have strongly favoured a response strategy based on self-blame and local mitigation, rather than other-blame and protest of industrial nations. I argue that this strategy does not stem from ignorance or disempowered pragmatism, but from a moral reading of climate change consonant with Marshallese values. Bringing together literature on traditionalism, entropy, and the cultural cognition of risk, I demonstrate that Marshallese reactions to climate change are intelligible in light of a vigorous pre-existing narrative of self-inflicted cultural decline. Climate change becomes framed as both a cause and a consequence of weakening custom, the over-reliance on foreign things, transforming global warming into a locally resonant, and indeed ideologically appealing, risk. Based upon this case study, I sketch a ‘trajectorial theory of risk perception’ and accompanying research agenda.